Rancang Bangun Website Sistem Informasi Praktikum Jurusan Teknik Informatika Univeritas Palangka Raya - Widiatry, Widiatry (STMIK Palangkaraya, 2016)
Department of Informatics Engineering at the University of Palangkaraya (UPR), particularly in academic, for processing and management of practicum data by manually or uncomputerized. In the scheduling process by manually such as selecting an empty class schedule to be able to do practicum. In designing the make of this website used software development methods, Waterfall, consisting of five stages, that is Communication, Planning, Modeling, Construction, and Deployment.This website uses Algorithm Depth First Search (DFS). Designing Website Information Systems Practicum is developed with the purpose as an information medium that can provide information such as schedule of data practicum and registration practicum for college students, can help lab assistant in registering the lab, managing attendance list and practicum scores, help head of the laboratory in monitoring the implementation of practicum, and can assist administrators in making the practicum schedule.